Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsami.8b17555
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Template Method for the Fabrication of Gelatin-Based Scaffold with a Controllable Pore Structure

Abstract: The porous microstructure of scaffolds is an essential consideration for tissue engineering, which plays an important role for cell adhesion, migration, and proliferation. It is crucial to choose optimum pore sizes of scaffolds for the treatment of various damaged tissues. Therefore, the proper porosity is the significant factor that should be considered when designing tissue scaffolds. Herein, we develop an improved emulsion template method to fabricate gelatinbased scaffolds with controllable pore structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 70 publications
(109 reference statements)
1
38
0
Order By: Relevance
“…Due to the amphiphilic nature of gelatin-graft-PNIPAM as a continuous phase, they managed to incorporate an internal phase of up to 90% without the use of any surfactants. Recently Yuan et al (2019) reported the fabrication of gelatin PolyHIPEs with 92% porosity by two-step crosslinking and freeze-drying. Alginate, a polysaccharide derived from seaweed, is another biomaterial that can be used to fabricate PolyHIPE scaffolds (Barbetta et al, 2009;Zhou et al, 2013).…”
Section: Hydrophilic Polymers For the Fabrication Of O/w Polyhipesmentioning
confidence: 99%
“…Due to the amphiphilic nature of gelatin-graft-PNIPAM as a continuous phase, they managed to incorporate an internal phase of up to 90% without the use of any surfactants. Recently Yuan et al (2019) reported the fabrication of gelatin PolyHIPEs with 92% porosity by two-step crosslinking and freeze-drying. Alginate, a polysaccharide derived from seaweed, is another biomaterial that can be used to fabricate PolyHIPE scaffolds (Barbetta et al, 2009;Zhou et al, 2013).…”
Section: Hydrophilic Polymers For the Fabrication Of O/w Polyhipesmentioning
confidence: 99%
“…The particle size and morphology of the microspheres are affected by many factors in the emulsification process, such as oil−water ratio, stirring speed, and concentration of sodium alginate. 46 Besides, the particle size and morphology of the resulting microspheres are related to the adding way of cross- link agent too. Uniform particle size of microspheres makes drug-release process controllable and reproducible, which is beneficial to predict the release kinetics of drugs.…”
Section: Resultsmentioning
confidence: 99%
“…The mouse osteoblasts (MC3T3-E1) and mouse myoblasts (C2C12) were used to evaluate the cytocompatibility of samples. The cytotoxicity of samples was evaluated by traditional CCK-8 methods. , The culture medium was high-glucose Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and 1% antibiotics (penicillin and streptomycin). The ultraviolet-sterilized samples were immersed in culture medium for 24 h at 37 °C to obtain the extraction liquid.…”
Section: Methodsmentioning
confidence: 99%